2013
DOI: 10.1111/jpc.12463
|View full text |Cite
|
Sign up to set email alerts
|

Cholangitis in children with biliary atresia: Health‐care resource utilisation

Abstract: The knowledge about the incidence and cost of cholangitis will allow physicians to counsel parents of children newly diagnosed with biliary atresia and to better prepare them both emotionally and financially for what to expect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
0
16
0
2
Order By: Relevance
“…Postoperatively, ascending cholangitis is a common complication. Lee et al 24 reported that 27 (64%) of 42 patients experienced at least 1 episode of cholangitis after Kasai operation. Most patients in their cohort experienced multiple episodes of cholangitis requiring hospitalization, with an average length of stay of 15 days.…”
mentioning
confidence: 99%
“…Postoperatively, ascending cholangitis is a common complication. Lee et al 24 reported that 27 (64%) of 42 patients experienced at least 1 episode of cholangitis after Kasai operation. Most patients in their cohort experienced multiple episodes of cholangitis requiring hospitalization, with an average length of stay of 15 days.…”
mentioning
confidence: 99%
“…Although Escherichia coli and Klebsiella pneumoniae seem to be the more prevalent bacteria found to cause episodes of cholangitis at the time of admission, 11 we did not know whether this would still be the case for bactDNA. Therefore, the aims of the current study were to explore the pattern of bactDNA in patients with cholangitis and its clinical significance for cholangitis.…”
mentioning
confidence: 57%
“…Анализ J. Lee и соавт. [20] показал, что 51,5% эпизодов холангитов возникают в первые 180 дней после операции, а 21,6% -между 180-м и 365-м днями, 11,3% -между 12-м и 18-м месяцами, 15,5% -с 18 до 24 мес.…”
Section: рис 3 продолжительность жизни детей с нативной печенью: крunclassified